2017
DOI: 10.5123/s1679-49742017000200013
|View full text |Cite|
|
Sign up to set email alerts
|

Tuberculose e diabetes: relacionamento probabilístico de bases de dados para o estudo da associação entre ambas doenças

Abstract: the cases found had similar profile to those registered on Sinan-TB and the probabilistic linkage of data from different information systems enabled the detection of cases not captured by surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
10

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 0 publications
2
8
0
10
Order By: Relevance
“…Concerning radiological examinations, some studies found no differences in X-ray patterns suspicious for pulmonary tuberculosis among people with and without diabetes 31,32 , unlike the results from other investigations that showed atypical radiographic characteristics in individuals with comorbidity 8,[33][34][35] . In this study, individuals with suspicious chest X-ray results had a greater association with comorbidity when compared to individuals who presented normal results.…”
Section: Discussionmentioning
confidence: 80%
“…Concerning radiological examinations, some studies found no differences in X-ray patterns suspicious for pulmonary tuberculosis among people with and without diabetes 31,32 , unlike the results from other investigations that showed atypical radiographic characteristics in individuals with comorbidity 8,[33][34][35] . In this study, individuals with suspicious chest X-ray results had a greater association with comorbidity when compared to individuals who presented normal results.…”
Section: Discussionmentioning
confidence: 80%
“…The Pan American Health Organization points out that DM makes a person three times more likely to acquire TB, in accordance to the fact that DM was the third morbidity most commonly associated to TB in this study. Authors also state that, in addition to being a risk factor for TB, DM contributes to bring forth latent cases (13)(14) . Rev Gaúcha Enferm.…”
Section: Discussionmentioning
confidence: 99%
“…Studies (9,14) pointed out that the presence of comorbidities is a predicting factor for the unsuccessful treatment of cases of TB. However, in this study, no comorbidity had a statistically significant association with a negative outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Ainda que os dois grupos populacionais estudados tenham revelado a ausência de comorbidade, quando se destaca especificamente o diabetes mellitus (DM), verificou-se maior incidência no grupo de mulheres. Os pacientes com diabetes têm mais chances de contrair a TB ativa, inclusive porque a DM pode interferir no metabolismo da medicação contra a TB (Abreu et al, 2017). Alguns estudos realizados em diversos países e em outras regiões do…”
Section: Dificuldades No Tratamentounclassified
“…Brasil investigaram a associação entre o DM e a TB e mostram que os homens se destacam com o maior percentual (Marks, 2011;Abreu et al, 2017;Barron et al, 2018;Saktiawati, Subronto, 2018;Hayashi, Chandramohan, 2018), à exemplo de estudo realizado na cidade da Beira, D i s c u s s ã o | 132…”
Section: Dificuldades No Tratamentounclassified